2003
DOI: 10.1046/j.1365-2370.2003.00395.x
|View full text |Cite
|
Sign up to set email alerts
|

The HLA‐DRB, ‐DQB polymorphism and anti‐insulin antibody response in Slovenian patients with type 1 diabetes

Abstract: A combination of specific HLA class II antigens and the presence of type 1 diabetes (T1D)-related antibodies has a high positive predictive value for T1D but low sensitivity. The aim of the present study was to determine the frequencies of HLA-DRB-DQB deduced haplotypes associated with susceptibility and protection in Slovenian patients with established T1D, to evaluate the relationship between the HLA-DRB1-QBP-DQB1 haplotypes and the presence of insulin autoantibodies (IAA) and glutamic acid decarboxylase ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
1
6
0
1
Order By: Relevance
“…In number of previous studies, C*07 was often found in combination with B*07 and DRB1*15:01 , forming second most common haplotype in many Caucasian populations. It was shown that DRB1*15:01‐DQB1*06:02 conferred protection against T1D . Interestingly, in this study, this protective effect could not be proven to extend to C*07 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In number of previous studies, C*07 was often found in combination with B*07 and DRB1*15:01 , forming second most common haplotype in many Caucasian populations. It was shown that DRB1*15:01‐DQB1*06:02 conferred protection against T1D . Interestingly, in this study, this protective effect could not be proven to extend to C*07 .…”
Section: Discussionsupporting
confidence: 91%
“…While DQ8 conveys higher risk for T1D than DQ2 (9) in CD approximately 90% of the patients carry the DQ2 (10). DQ8 was also a predominant risk factor in Slovenian patients with T1D (11) and DQ2 in patients with CD (12).…”
Section: Introductionunclassified
“…A group of 37 individuals with T1D and CD, diagnosed according to the revised European Society of Pediatric Gastroenterology and Nutrition (ESPGAN) criteria with histological conformation (29), was compared with a well‐defined group of 67 individuals with only T1D, previously typed for HLA‐DRB1 and DQB1 (30). All 37 individuals with T1D and CD were diagnosed with CD after the onset of T1D.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, some haplotypes, such as HLA‐DR2 (DRB1*15:01 – DQA1*01:02 – DQB1*06:02), which is also the most common DR–DQ haplotype in Caucasians, strongly contribute to protection from T1D in a dominant manner over susceptibility haplotypes (Ettinger et al ., , ; Cerná, ; Noble & Valdes, ; Noble & Erlich, ). A limited number of studies in Iranian population indicate that the prevalence of risk‐associated and/or protective HLA alleles for T1D (Sayad et al ., ; Rabbani et al ., ) is almost in line with various reports from other Caucasians (Noble et al ., ; Saruhan‐Direskeneli et al ., ; Petrone et al ., , ; Battelino et al ., ; Hermann et al ., ; Erlich et al ., ; Ilonen et al ., ; Cifuentes et al ., ). Notably, observation of few differences between results of those limited studies in Iranian population and other Caucasians or even some Asian population is reasonable due to several contributing factors including ethnic origin of subjects in each study, sample size, different incidence of T1D in each region and other unknown factors (Park et al ., ; Park & Eisenbarth, ; Park, , ; Polychronakos & Li, ).…”
Section: Introductionmentioning
confidence: 99%